Forensic investigation of a slender high-rise structure subject to dynamic wind conditions - Lim, E S; Lee, H E; Liew, M S (IOP conference series. Earth and environmental science, 2019)
The forensic engineering of a collapsed reinforced concrete fin wall structure is presented in this paper. The investigative process considers the assessment between the actual wind load conditions structure during the time of collapse against the actual structural capacity of the structure. Three design conditions are considered in this study; in-situ wind speed during the time of incident, wind speed used by the design consultant and wind speed recommended by Jabatan Meterologi Malaysia (JMM) in 1995, which was the time of design. The structure is both analyzed from a static analysis and dynamic time history analysis standpoint. It was found that the amplification factor due to the near resonance of wind energies between 0.25-0.30 Hz and the natural frequency of the structure, 0.27Hz. This resulted in a amplification of 1.8 over quasi-static loading conditions as governed by CP3 design code. It was further found that the dynamic wind loading imposed against the structure was 10% less from the actual capacity of the structure determined via nonlinear pushover analysis. This result is at best marginal considering the inelastic performance of the structure and the actual as-built condition of the structure; giving strong indication to the role of resonance in the collapse. The technical interpretation of the design codes leading to the responsibilities of the design consultant are not discussed in this paper.